Processing and characterizations of Bi2O3/BaTiO3 ceramic - Wanwilai C. Vittayakorn (2018)
The objective of this work is to provide the process for making BaTiO 3 -based ceramics by adding bismuth oxide (Bi 2 O 3 ) into the system. The attention is also focused on synthesis conditions, where sintering temperature exhibits a pronounced effect on phase formation, density, microstructure and dielectric properties of BaTiO3 ceramics doped with different contents of Bi 2 O 3 nanoparticles. The phases of BaTiO 3 -based ceramics have been prepared by solid state reaction using different Bi 2 O 3 amount and characterized by X-ray diffractometry, Archimedes's method, scanning electron microscopy and dielectric spectroscopy. The results show that single phase of BaTiO 3 with no evidence of secondary phase forms in all samples. Abnormal grain growth was found in pure BaTiO 3 ceramic with 37.30 μm of average grain size. After added Bi 2 O 3 nanoparticles into system, the grain size significantly decreases and the sintering temperature of BaTiO3-based ceramics efficiently reduces without degrading the dielectric characteristics. © (2013) Trans Tech Publications, Switzerland.